An assessment of the environmental compliance monitoring capacity of the Department of Minerals and Energy, Eastern Cape - Watkins, Deidre Ann (Rhodes University, Faculty of Commerce, Investec Business School, 2009)
One of the greatest challenges facing the world today is integrating industrial activities such as mining with environmental integrity and social concerns. Monitoring is fundamental to environmental management, both to assess the adherence to standards and to allow environmental managers to learn from practical experiences. However, a problem arises when the regulatory authorities cannot keep up with their mandate of enforcement and compliance monitoring. This research examined how the Department of Minerals and Energy (DME) implements the concept of sustainable development in the mining sector of the Eastern Cape (EC) and, more specifically, the extent to which the Mine Environmental Management (MEM) section is able to effectively monitor compliance of mining operations with environmental legislation. This was the first systematic compilation of statistical data for the DME, and presents the first study in the EC regional office in terms of environmental sustainability. Results indicate that there has been a sustained increase in mining activity over the past three years, possibly as a result of the boom in the construction industry and the accelerated road maintenance and improvement programmes in the Eastern Cape. Mining applications received by the DME have increased by 47% from 2006 to 2007 (January-May) and by a further 100% from 2007 to 2008. In addition to the increasing number of mining concerns being established, 98 mining concerns will need to apply for the conversion of their old order rights to new order rights by the 1st May 2009. Mining in the province is predominantly small scale with mining permits (mined areas less than 1.5Ha) making up 52.3% of all applications, with larger mining concerns contributing 29.3% and prospecting contributing the remaining 18.4%. In terms of compliance inspections, the EC regional office is required to conduct 120 environmental compliance inspections annually in terms of contributing to sustainable development. The MEM section exceeded this target since 2003. However, when the number of operational mines is considered, 120 inspections per year equates to one mine being visited, on average once every four years (based on 2008 data). Based on projected figures (number of compliance audits and number of operational mines) for 2009, the DME's target of 150 inspections for 2009/10 combined with the limited staff D. Watkins "“ MBA Dissertation 2008 capacity will, at best, mean that mines would be inspected once in seven years. However, the target of 150 inspections will not actually even cover the expected number of EMP evaluation inspections. This has serious implications in terms of regulating the compliance of the mining concerns with their EMPR's. The low level of compliance monitoring can be directly related to staff capacity and logistics problems at the regional office as well as provincial targets being based on staff capacity rather than the number of operational mines. Thus, considering potential environmental damage associated with mining operations and the capacity constraints of the MEM to conduct frequent compliance audits, it is likely that mining operations will have negative implications for sustainable development in the region. Currently there are many challenges facing the DME in terms of contributing positively to sustainability in the mining sector and there is a need to base future actions on the idea of continuous improvement and ultimately progress.
Keywords: South Africa. Dept. of Mineral and Energy Affairs; Mines and mineral resources -- South Africa -- Eastern Cape; Mineral industries -- South Africa -- Eastern Cape; Mineral industries -- Social aspects -- South Africa -- Eastern Cape; Mineral industries -- Environmental aspects -- South Africa -- Eastern Cape; Mines and mineral resources -- Social aspects -- South Africa -- Eastern Cape; Mines and mineral resources -- Environmental aspects -- South Africa -- Eastern Cape; Environmental auditing -- South Africa -- Eastern Cape